Poor dietary quality is Nigeria’s key nutrition problem - Ecker, Olivier; Comstock, Andrew R.; Babatunde, Raphael O.; Andam, Kwaw S. (Michigan State University, 2020)
Nigeria faces a growing triple burden of malnutrition. First, chronic childhood undernutrition remains stubbornly high. Nationwide, 36.8% of children under five years were estimated to be stunted in 2018—only slightly down from 40.8% in 2008. This corresponds to an annual average decline of less than 0.4 percentage points over the last decade and was almost exclusively due to a reduction in the prevalence of child stunting in urban areas (Table 1). Second, micronutrient malnutrition, including iron deficiency anemia, is extremely widespread among young children and women of reproductive age. While the prevalence rate of anemia among children under five years slightly declined in rural areas between 2010 and 2018, it substantially increased in urban areas. Third, overweight and obesity among adults has been rising rapidly in both urban and rural areas. Over the last decade, the national prevalence rates of overweight and obesity (the extreme form of overnutrition) among nonpregnant women 15 to 49 years of age increased faster than the rate of child stunting decreased, driving the growth of the triple burden. Obesity significantly increases the risk of diet-related non-communicable diseases (NCDs) such as type-2 diabetes, cardiovascular diseases (like heart attack and stroke), and hypertension. The root cause of all forms of malnutrition is poor dietary quality, while poor water, sanitation, and hygiene (WASH) conditions aggravate malnutrition.